Ajaran Welas Asih dalam Al Qur an - fahman, mundzar (Universitas Nahdlatul Ulama Sunan Giri, 2017)
The majority of Muslims are very confident that Islamic religion teaches compassion and nonviolence to others. They know and believe that in the Qur an and the Sunnah of the Prophet, there are many commands and suggestions for a more compassionate (merciful). But the big problem is, there are still small groups of Muslims who show violent attitudes. They are often referred to as radical Islam. They did not hesitate to commit acts of terrorism to kill others. The number of followers of radical secte is small. Violence, or acts of terrorism that they did, are not routine, but only temporary. However, their action is more easily affect to the public opinion of the Islamic teaching. The world view that Islam preaches violence, cruel, and far and opposite from feeling compassion for others. View of the Islam and the Muslims are now as represented by the President of the United States Donald Trump. President Trump issued a policy prohibiting citizens from seven Muslim-majority countries to enter to the territory of the United States. The reason President Trump, the seven countries has been a contributor to international terrorists. Seven countries were Iraq, Iran, Libya, Somalia, Sudan, Syria, and Yemen. So, for the majority of moderate Muslims, have to continue to give enlightenment to the world, including to the Muslim minority radical groups. Enlightenment through many varieties of media, including paper media. The goal, for the world view of Islam can be changed from negative to positive view; actually that Islam is not as a terrorist, but Islam is polite and humane, compassionate Islam (love and compassion) to fellow humans. Even compassion for nature. Its flow is expected to turn into a radical polite and forgiving. Islam is rahmatan lil alamin, Islam is not la'natan lil alamin. This paper is intended as part of the provision of such enlightenment. The results of the study authors at the content of Al Qur an, apparently very many verses that contain messages of affection. Islam teaches the Muslims to compassionate to one another, not only to theirself. Not only to family and neighbors, but to all mankind, Muslims or non-Muslims. In fact, Islam ordered his people to love nature, by not doing the destruction of the environment. Prophet Muhammad SAW provide exemplary to his people a lot about patience, about how easy to forgive the enemies of Islam. And, finally, many of the enemies of Islam become a good Muslim.